(untitled) (Swiss Medical Weekly, 2021)
AIMS OF THE STUDY: The Swiss healthcare system is highly ranked, given its unrestricted access to specialised care and short waiting lists for surgery. However, the need for anaesthetic and surgical care is escalating owing to the increasing size and ageing of the Swiss population. In addition, to address the persistent and recurrent SARS-CoV-2 pandemic crisis, the speciality of anaesthesia is under tremendous pressure to maintain an effective workforce in order to address population needs. The current number, characteristics and future evolution of the physician anaesthesia workforce in Switzerland are currently unknown. The purpose of this study was to assess the size and professional and sociodemographic characteristics of the current anaesthesia workforce in Switzerland and to forecast its development up to 2034. METHODS: We performed a cross-sectional study using a 150-item questionnaire prepared by the National Anaesthesia Workforce Study Group (NAWOS). We included all physicians (trainees and certified) practising anaesthesia in Switzerland. We collected demographic and professional information, such as the current position, hospital characteristics, workload, number of shifts and future life plans. We built a computer-based Markov model with Monte Carlo simulations to project both supply and demand for physician anaesthesia provider positions. RESULTS: Of the 2661 distributed questionnaires, 1985 (74.2%) were completed and returned. We found that the average age of anaesthesiologists practising in Switzerland was 45.2 years, with 44.3% of them being women and 76.9% holding a Swiss specialist title. Only 59.6% of respondents worked full time. The forecasting model showed a steady increase in the number of anaesthesiologists retiring by 2034, with 27% of full-time equivalent jobs being lost in the next 8 years. Even if existing full-time equivalent training positions are all filled, a gradual deficit of anaesthesiologists is to be expected after 2022, and the deficit should culminate in 2034 with a deficit ratio of 0.87. CONCLUSIONS: Due to the upcoming high retirement rate of anaesthesiologists, Switzerland is likely to face a shortage of anaesthesiologists in the near future. To compensate for the shortage, the country will likely increase its reliance on medical staff trained abroad. Southern and eastern cantons of Switzerland are particularly at risk, given that they already heavily rely on foreign anaesthesia workforce. This reliance should be considered a national priority because anaesthesiologists are heavily involved in both the treatment of patients with respiratory complications of SARS-CoV2 infection and the care of surgical patients, the number of which is expected to rise steadily in upcoming years.